The Impact of Regular Diet Recovery on Postoperative Rehabilitation After Elective Cesarean Section - Caihong Hu; Kuilin Fei; Yuelan Liu; Xiaoe Jiang; Wenjing Yong; Weishe Zhang; Ping Li; Yang Pan; Jue Li (Maternal-Fetal Medicine)
Abstract. Objective. To determine the role of regular diet recovery after restoration of normal muscle strength of both lower extremities in promoting postoperative recovery in women undergoing elective cesarean section. Methods. This was a prospective observational cohort study. Patients who underwent elective cesarean section at Xiangya Hospital, Central South University, from October 2022 to December 2022, were categorized into two groups based on the duration of postoperative fasting: the observation group resumed eating after regaining lower extremity muscle strength, while the control group adhered to traditional postoperative fasting guidelines, waiting 6 hours before eating. Primary outcomes included postoperative pain levels assessed by visual analog scale (VAS) pain scores and time to first flatus. Demographic characteristics, time to first lactation, hospital stay length, and patient satisfaction were also assessed. Statistical analysis was conducted using Student’s t test and Chi-squared test, with significance set at P < 0.05. Results. Out of a total of 300 patients, 240 were included in the analysis, comprising 112 in the control group and 128 in the observation group. There were no significant differences in baseline demographic characteristics. The median values of the first flatus time and the first lactation time were 33.37 ± 1.22 vs. 18.06 ± 6.34 hours (P = 0.003) and 26.34 ± 8.21 vs. 7.05 ± 1.26 hours (P = 0.001) in the control and observation groups, respectively. The median hospital stay duration in the control and observation groups was 6.54 ± 0.53 vs. 4.84 ± 0.18 days (P = 0.000), respectively. Median postoperative VAS pain scores and patient satisfaction values were 8.57 ± 0.11 vs. 4.91 ± 0.27 (P = 0.000) and 9.36 ± 0.16 vs. 9.72 ± 0.08 (P = 0.005) in the control and observation groups, respectively. There were no statistically significant differences in other postoperative outcomes, such as intestinal obstruction, infection, and readmission within 42 days (P > 0.05). Conclusion. Food intake after restoration of lower extremity muscle strength improves first flatus, relieves postoperative pain, shortens hospital stay, and enhances satisfaction after elective cesarean section, without adverse effects. It is crucial for postoperative rehabilitation and should be encouraged.